The Differential DRP1 Phosphorylation and Mitochondrial Dynamics in the Regional Specific Astroglial Death Induced by Status Epilepticus - Ko, Ah-Reum; Hyun, Hye-Won; Min, Su-Ji; Kim, Ji-Eun (Frontiers in Cellular Neuroscience, 2016)
The response and susceptibility to astroglial degenerations are relevant to the distinctive properties of astrocytes in a hemodynamic-independent manner following status epilepticus (SE).Since impaired mitochondrial fission plays an important role in mitosis, apoptosis and programmed necrosis, we investigated whether the unique pattern of mitochondrial dynamics is involved in the characteristics of astroglial death induced by SE. In the present study, SE induced astroglial apoptosis in the molecular layer of the dentate gyrus, accompanied by decreased mitochondrial length. In contrast, clasmatodendritic (autophagic) astrocytes in the CA1 region showed mitochondrial elongation induced by SE. Mdivi-1 (an inhibitor of mitochondrial fission) effectively attenuated astroglial apoptosis, but WY14643 (an enhancer of mitochondrial fission)aggravated it. In addition, Mdivi-1accelerated clasmatodendritic changes in astrocytes. These regional specific mitochondrial dynamics in astrocytes were closely correlated with dynamin-related protein (DRP1, a mitochondrial fission protein) phosphorylation, not optic atrophy 1 (a mitochondrial fusion protein) expression. To the best of our knowledge, the present data demonstrate for the first time the novel role of DRP1-mediated mitochondrial fission in astroglial loss. Thus, the present findings suggest that the differential astroglial mitochondrial dynamics may participate in the distinct characteristics of astroglial death induced by SE.